State Versus Farmers: Potential for Agrarian Conflict in Algeria - Ikrame, El Ahmar; Ritonga, Fajar Utama (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2024)
This article explains potential conflict agrarian between countries against farmers in Algeria with use approach study qualitative in a way critical and systematic. Some the sources used, namely experience direct researchers, books, journals, and works scientific-scientific others. Research results show beginning start birth potential conflict agrarian State with farmers namely since the beginning of the colonial era France in Algeria and continuing until day. Country (government) Algeria after free from shackles colonization French make an effort advance agriculture in Algeria. Intention both those promoted by the government Algeria This precisely produce on the contrary, namely give birth to potential conflict agrarian which is not end between the State and farmers, such as regulation land that is not clearly, the infrastructure is not established, profitable capital loans adjacent party (country), and failed harvest (famine).